Can Cognitive Control and Attentional Biases Explain More of the Variance in Depressive Symptoms Than Behavioral Processes? A Path Analysis Approach - Krings, Audrey; Simon, Jessica; Carré, Arnaud; Blairy, Sylvie (Frontiers in Psychology, 2022)
Background: To investigate the usefulness of combining behavioral activation (BA) with another cognitive psychological treatment, this study explored the proportion of variance in depressive symptoms explained by processes targeted by BA (activation, behavioral avoidance, anticipatory pleasure and brooding), and processes targeted by cognitive control training (cognitive control, attentional biases and brooding). Methods: Five hundred and twenty adults were recruited. They completed a spatial cueing task as a measure of attentional biases and a cognitive task as a measure of cognitive control and completed self-report measures of activation, behavioral avoidance, anticipatory pleasure, brooding and depressive symptoms. With path analysis models, we explored the relationships between these predictors and depressive symptoms. Results: BA processes were significant predictors of depressive symptoms, and activation partially predicted anticipatory pleasure, which in turn predicted depressive symptoms. However, cognitive control and attentional biases predicted neither brooding nor depressive symptoms. A comprehensive model including all processes fit the data but did not explain more of the variance in brooding or depressive symptoms than a model including only BA processes. Limitations: The spatial cueing task was associated with low reliability and the use of a non-clinical sample limited the generalizability of the conclusions. Conclusion: Activation, behavioral avoidance, brooding and anticipatory pleasure are relevant processes to target in order to reduce depressive symptoms, while cognitive control and attentional biases are not. The results contradict the notion that using cognitive training might be a promising add-on treatment to BA.